Liberia - Employment and Pro-Poor Growth - World Bank (World Bank, 2012)
Fourteen years of civil conflict (1989-2003) have destroyed Liberia's social and economic infrastructure and brought the economy nearly to a halt. Workers who came of age during the conflict are largely unskilled, and the supply of workers exceeds demand by a substantial margin. The negative effects of unemployment, underemployment, and low productivity on economic growth have made employment the most urgent demand of the population and the top priority for Government action. This report offers guidance to the Government of Liberia in its development of a more strategic approach toward increasing productivity and employment, in order to achieve its pro-poor growth objectives. This report includes seven sections: employment is key for poverty reduction; one in five workers is unemployed or underemployed; the structure of Liberia's economy limits prospects for formal sector employment; transformation of the agriculture sector is essential for pro-poor growth; investment and job growth in the formal sector are constrained by three main factors; labor-intensive public works programs are necessary for the very poor; and education and training must be improved to enhance employability.